Creating online, inclusive spaces for learning: ‘Study Together’ with the personal learning advice service - Janet Lindley; Mary-Jayne Wilton (Journal of Learning Development in Higher Education)
There is a wealth of scholarship on the benefits of synchronous writing sessions for staff and students in higher education (Kornhaber et al., 2016; Eardley et al., 2021; Morley and Aston, 2023). In the Personal Learning Advice (PLA) Service at the Open University UK (OU), we developed bespoke, online study spaces for students from groups currently underrepresented in higher education – known as ‘Study Together’ sessions. The sessions prioritise students from minoritised ethnic groups, students with disabilities, and students with mental health needs who are at risk of poorer study outcomes. This presentation charted the development of Study Together in response to student feedback and evaluation and sought to show the value of ‘targeted’ invitations to engage students with spaces for learning development. Our presentation began by outlining the rationale for a 2022-23 Study Together pilot and its impact on community and belonging for students with mental health declarations (Lavery et al., 2023). We shared our approach to hosting Study Together and the techniques used to create an inclusive, productive study space; we showed how these approaches allowed us to incorporate timed study bursts and reflective practice, building positive study habits among students. Finally, we presented findings from the evaluation of Study Together in 2023-24 and situated this within the wider literature on the benefits of virtual communities of practice for learning. Our presentation spoke directly to the ALDcon24 theme ‘Building inclusive learning development spaces’ and invited delegates to consider the place of virtual, guided study spaces in their own practice.